Nanostructured materials for photoelectrochemical water splitting - Chang, Jih-Hsing; Kumar, Mohanraj; Nayak, Arpan Kumar (IOP Publishing, 2021)
Photoelectrochemical water splitting has been identified as a suitable and sustainable approach to address two of the main issues facing humanity: environmental protection, and clean and sustainable energy production. Nanostructure-based photoelectrochemical water splitting is a highly promising process for converting solar energy into hydrogen energy. This reference text presents the latest research and developments in the area of photoactive nanostructured materials and their photoelectrochemical water splitting for applications in environmental protection, clean energy production and chemical amalgamation/processing.
Keywords: Photoelectrochemistry.; Water -- Electrolysis.; Nanostructured materials.; Materials science.; Materials.; elektronické knihy; electronic books